Efeitos do cacau, flavonoide epicatequina e chocolate, na citotoxicidade, genotoxicidade e radioproteção, sobre o radiofármaco Iodo-131, em células de hepatoma humano HepG2/C3A - Heck, Michele Cristina (2014)
Cacao, Theobroma cacao, has been consumed for more than 1000aC., However, in recent years, the cocoa and cocoa products have attracted the interest of the scientific community for being among the richest foods in flavonoids such as epicatechin, and its beneficial health effects. In this sense, the radio-protective are usually antioxidants such as flavonoids, which have the ability to protect the living tissue against the damaging action of free radicals. The radioactive Iodine-131 (I-131), is widely used for the diagnosis and treatment of hyperthyroidism and thyroid cancer, for evaluation of hematologic disorders and as a treatment option for hepatocellular carcinoma, however, it emits radiation ionizing radiation, which can cause serious damage to normal cells, particularly for interacting with the environment where cellular constituents are such as water, leading to production of free radicals. Therefore, the aim of this study was evaluated the cytotoxic and genotoxic effects of cocoa (Theobroma cacao L.), its derivative semidark chocolate and its flavonoid epicatechin, and investigate its cytoprotective, antigenotoxic and radio-protective effects in relation to radioisotope Iodine-131 in the test system in vitro culture of human liver cells metabolizing HepG2/C3A using MTT Assay, Cell Viability with Trypan Blue Assay, Kinetics of Cell Proliferation and Comet Assays. The results indicate that cocoa, epicatechin and chocolate affect cell metabolism at high concentrations. Cocoa (Ca ≥ 150μg/mL) reduces mitochondrial activity in time of 48 hours; epicatechin (Epi ≥ 145μg/mL) reduces the activity time of 72 hours; and chocolate within 48 hours stimulates mitochondrial activity (≥ Ch 150μg/mL). However, at lower concentrations (Ca: 1, 10, 50 and 100 μg/mL, Epi: 0.29, 2.9, 14.5 and 72.5 μg/mL, Ch 1, 10, 50 and 100μg/mL) no differences in the kinetics of viability and proliferation were observed. The Comet assay showed that the concentrations of 14.5 and 72.5 μg/mL, induce more severe damage compared to treatments with cocoa, chocolate and epicatechin in the lowest concentration (2.9μg/mL), however, only the concentration 72.5μg/mL epicatechin, exerted genotoxic activity. With respect to radiation protection, treatment with 10μCi of I-131 reduced the mitochondrial activity, viability and cell kinetics of proliferation. The radioprotective effect was observed by increased mitochondrial activity, cell viability and proliferation kinetics in the groups treated with the associated I-131 compounds, (1μg/mL cocoa and I-131; 2.9μg/mL epicatechin and I -131; 1μg/mL chocolate and I-131). The compounds tested along with I-131, significantly reduced the damage on DNA, by Comet Assay. Thus, the results of this study showed that cocoa and semidark chocolate showed no genotoxic activity, the amount and how it is consumed, as well as its flavonoid epicatechin. Instead, the data demonstrate that these compounds have a radioprotective effect on the damage induced by I-131. Thus, the consumption of cocoa and its derivative, the chocolate shows up as an important source compounds with protective effects, and accessible for emission, especially for those who are exposed to doses of I-131 opportune diagnosis or occupationally.